Gelation dynamics of ionically crosslinked alginate gel with various cations - Gwon, Seok Hyeon; Yoon, Juil; Seok, Hyun Kwang; Oh, Kyu Hwan; Sun, Jeong-Yun (SPRINGER, 2015)
Alginates can be crosslinked with multivalent cations, leading eventually to hydrogel formation. The properties of alginate gel depend on its lock structure, monomeric composition, concentration of polymer and cross linker. Among these, the properties of ionically crosslinked alginate gel can be greatly affected by multivalent cations as cross-linker. Knowledge of gelation dynamics by multivalent cations allows control over gelation characteristics, such as modulus of gel and the time required for equilibrium state, and healing properties. We have studied gelation dynamics of ionically crosslinked alginate gel. According to different types of anions bound with cations, gelation time and equilibrium viscosity was changed due to the solubility kinetics of the cation. The equilibrium viscosity is increased as the size of the cations increased even though the cations have same valency. A theoretical model is introduced to interpret dynamic change of viscosity during gelation.